2019
DOI: 10.24215/18536387e016
|View full text |Cite
|
Sign up to set email alerts
|

Las termitas como agentes aturales de alteraciones tafonómicas postdepositacionales en un esqueleto humano del sitio arqueológico Toca do Enoque (Piauí, Brasil)

Abstract: Las termitas son insectos que aparecen muchas veces en contextos arqueológicos en Brasil y casi nunca son objeto de estudio como procesos naturales de formación de los depósitos y contextos arqueológicos. La probabilidad de que se encuentren marcas de estos insectos modificadores de carcasas de animales y humanos en sitios arqueológicos en Brasil y en Sudamérica hace pertinente su estudio. A partir de una aproximación teórica - metodológica que comprende la Icnoarqueología y la Arqueoentomología Funeraria, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
1
1
3
Order By: Relevance
“…There was also a termite nest within the burial area. Although we observed partial termite damage on the bones of this individual, these natural agents were neither the main nor the only taphonomic agent responsible for the state of the body (Solari, Pessis, Martin, Barbosa, and Monteiro da Silva 2020): the slightly burned condition of some bones (mandible and left ulna) and the absence of several other bones were better explained by deliberate postfunerary anthropic action.…”
Section: Results: Evidence Of Disturbed Burials In Brazilcontrasting
confidence: 57%
See 1 more Smart Citation
“…There was also a termite nest within the burial area. Although we observed partial termite damage on the bones of this individual, these natural agents were neither the main nor the only taphonomic agent responsible for the state of the body (Solari, Pessis, Martin, Barbosa, and Monteiro da Silva 2020): the slightly burned condition of some bones (mandible and left ulna) and the absence of several other bones were better explained by deliberate postfunerary anthropic action.…”
Section: Results: Evidence Of Disturbed Burials In Brazilcontrasting
confidence: 57%
“…Toca do Enoque (Guidon and Luz 2009) was a funerary site occupied by preceramic hunter-gatherer groups during the Middle to Late Holocene, from 6620 ± 50 BP to 3430 ± 40 BP (Solari, Pessis, Martin, Barbosa, and Monteiro da Silva 2020:4). At the site, three human burials were found that contained a total of 12 individuals.…”
Section: Results: Evidence Of Disturbed Burials In Brazilmentioning
confidence: 99%
“…Nessa deposição, foi possível observar que, em algumas partes da fossa perturbada, foram registradas áreas queimadas, restos de fogueiras, carvões e cinzas abundantes, junto com alguns ossos parcialmente queimados do esqueleto. Ao mesmo tempo, ninhos de cupins foram observados na área da cova e grandes blocos de pedra foram achados entre os ossos dispersos do esqueleto (Luz, 2014;Solari et al, 2020c)…”
Section: Uma Descrição Geral Dos Sepultamentosunclassified
“…No entanto, ao contrário do sepultamento 1, após o que teria sido o fim do ciclo funerário do sepultamento 3, este último sofreu consideráveis perturbações pós-deposicionais de origem natural e antrópica. Por uma parte, a maioria dos ossos preservados apresentou sinais de bioerosão, marcas de alterações termíticas macroscopicamente observáveis, que permitiam reconhecer um padrão de dano no esqueleto compatível com a atividade de cupins subterrâneos da família Termitidae, endêmica da região neotropical do Nordeste brasileiro (Solari et al, 2020c).…”
Section: Seus Ossos Foram Localizados Aproximadamente No Centrounclassified
See 1 more Smart Citation